2000
DOI: 10.4049/jimmunol.165.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Duplicated DQ Haplotypes Increase the Complexity of Restriction Element Usage in Cattle

Abstract: The MHC of cattle encodes two distinct isotypes of class II molecules, DR and DQ. Unlike humans, cattle lack the DP locus and about half the common haplotypes express duplicated DQ genes. The number and frequency of DQA and DQB alleles means that most cattle are heterozygous. If inter- and/or intrahaplotype pairing of DQA and DQB molecules occurs, cattle carrying DQ-duplicated haplotypes may express more restriction elements than would be predicted by the number of expressed alleles. We are investigating wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 44 publications
4
55
0
Order By: Relevance
“…6). This is supported by recent publications showing that DQ molecules in cattle are relevant for peptide presentation to T helper cells in immune responses against FMDV-derived peptides (15), Babesia bovis (26), and Anaplasma marginale (6). Furthermore, FIG.…”
Section: Vol 83 2009 Anchor Residues Of Bovine Fmdv T-cell Epitopessupporting
confidence: 60%
“…6). This is supported by recent publications showing that DQ molecules in cattle are relevant for peptide presentation to T helper cells in immune responses against FMDV-derived peptides (15), Babesia bovis (26), and Anaplasma marginale (6). Furthermore, FIG.…”
Section: Vol 83 2009 Anchor Residues Of Bovine Fmdv T-cell Epitopessupporting
confidence: 60%
“…Although not directly tested, this result could be explained by intrahaplotype pairing of DQ␣ and DQ␤ chains, which has been previously observed for cattle (32).…”
Section: Discussionmentioning
confidence: 66%
“…Each haplotype expresses one nonpolymorphic DR␣ molecule, one polymorphic DR␤ molecule (DRB3), and one or more polymorphic DQ␣ and DQ␤ molecules when DQ is duplicated (reviewed in reference 33). Furthermore, in cattle DQ␣ and DQ␤ chains can form both inter-and intrahaplotype pairing (32,33), resulting in increased class II polymorphism. To determine whether responses of individual Thcell clones were restricted by DR or DQ molecules, T cells were cultured with specific antigen and autologous APC, APC fully matched for both DR-DQ haplotypes, APC matched for one DR-DQ haplotype, or APC mismatched for both haplotypes (Table 2).…”
Section: Vol 70 2002 a Marginale Msp1a T-cell Epitopes 5527mentioning
confidence: 99%
“…The fact that all individuals had more than two haplotypes suggested that these haplotypes did not arise from the same locus and, thus, could be regarded as evidence for the existence of gene duplication at the UTR of the ERP gene in E. sinensis. Gene duplications have been revealed in D-loop of mtDNA (Cjetva et al, 1992;Ludwig et al, 2000) and in many MHC loci, for example, the spotted seal (Phoca largha) DRB locus (Gao et al, 2015) and the cattle (Bos taurus) DQA and the DQB loci (Glass et al, 2000).…”
Section: Discussionmentioning
confidence: 99%